2022
DOI: 10.3390/ijerph19052829
|View full text |Cite
|
Sign up to set email alerts
|

Increased Odds for Depression and Antidepressant Use in the Inactive Spanish Population

Abstract: Introduction: Depression is a disabling mental illness and therefore also a serious public health problem. It affects 5% of the adult population in the world and is the leading cause of disability, with an annual cost of USD one trillion. In Spain, its prevalence is 13.4%, costing EUR 6000 million a year. Physical inactivity has been linked to an increase in depressive symptoms, with physical activity associated with an improvement in health-related quality of life. Objective: To calculate the odds ratio (OR) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…Depression prevalence was higher in the inactive groups, decreasing in the groups with higher PA frequency. Several studies support these results [ 15 , 16 , 37 , 38 ], stating that is mandatory to increase the importance of PA to reduce the likelihood of depression. Rosenbaum (2014) [ 22 ] reported that PA reduces depressive symptoms in people with mental illness.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…Depression prevalence was higher in the inactive groups, decreasing in the groups with higher PA frequency. Several studies support these results [ 15 , 16 , 37 , 38 ], stating that is mandatory to increase the importance of PA to reduce the likelihood of depression. Rosenbaum (2014) [ 22 ] reported that PA reduces depressive symptoms in people with mental illness.…”
Section: Discussionmentioning
confidence: 79%
“…Some examples of these policies could be guides and advice for families about PA, sports programs promoted by municipalities, educational centers and companies, policies to promote PA as a way of transportation, creating areas for the practice of PA, active aging programs, etc. These policies are aimed to increase the frequency of PA in all age groups, as inactivity has a potential risk for depression [ 15 , 16 ], and as we know, depression can appear at any age [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Between 0 and 7 days per week, or NS/NC). The PAI formula, the values it could take, as well as the way in which participants were grouped by PAL was described in previous publications) [ [31] , [32] , [33] ].…”
Section: Methodsmentioning
confidence: 99%
“…In the United States, for example, the use of antidepressants has increased from 10.6 to 13.8% in the last decade, with almost one in seven people taking antidepressants, and the rate of antidepressant use is even higher among women, with almost one in five women using antidepressants and even one in four women over the age of 60 taking antidepressants. The use of antidepressants in Australia and European countries is similar to that in the US [ 3 , 5 , 6 ]. The use of antidepressants can cause a variety of diseases.…”
Section: Introductionmentioning
confidence: 99%